The story keeper ebook - Wingate, Lisa (Carolina Heirlooms, 2014)
“ Not since To Kill a Mockingbird has a story impacted me like this.“ – COLLEEN COBLE , USA Today bestselling author of Seagrass Pier “Wingate is, quite simply, a master storyteller. Her story-within-a-story, penned with a fine, expressive style, will captivate writers and nonwriters alike.” – Booklist Successful New York editor, Jen Gibbs, is at the top of her game with her new position at Vida House Publishing – until a mysterious manuscript from an old slush pile appears on her desk. Turning the pages, Jen finds herself drawn into the life of Sarra, a mixed-race Melungeon girl trapped by dangerous men in the turn of the century Appalachia. A risky hunch may lead to T he Story Keeper ’s hidden origins and its unknown author, but when the trail turns toward the heart of the Blue Ridge Mountains, a place Jen thought she’d left behind forever, the price of a blockbuster next book deal may be higher than she’s willing to pay. A beautifully written contemporary novel with hints of romance Themes of forgiveness, family, returning home, and navigating brokenness Includes discussion questions for book clubs